Metabolically Healthy Obesity and Risk of All-Cause and Cardiovascular Disease Mortality - Hamer, Mark (Endocrine Society, 2012)
CONTEXT: Previous studies have identified an obese phenotype without the burden of adiposity-associated cardiometabolic risk factors, although the health effects remain unclear. OBJECTIVE: We examined the association between metabolically healthy obesity and risk of cardiovascular disease (CVD) and all-cause mortality. DESIGN AND SETTING: This was an observational study with prospective linkage to mortality records in community-dwelling adults from the general population in Scotland and England. PARTICIPANTS: A total of 22,203 men and women [aged 54.1 (SD 12.7 yr), 45.2% men] without known history of CVD at baseline. INTERVENTIONS: Based on blood pressure, high-density lipoprotein-cholesterol, diabetes diagnosis, waist circumference, and low-grade inflammation (C-reactive protein ≥ 3 mg/liter), participants were classified as metabolically healthy (0 or 1 metabolic abnormality) or unhealthy (two or more metabolic abnormalities). Obesity was defined as a body mass index of 30 kg/m(2) or greater. MAIN OUTCOME MEASURE: Study members were followed up, on average, more than 7.0 ± 3.0 yr for cause-specific mortality. Cox proportional hazards models were used to examine the association of metabolic health/obesity categories with mortality. RESULTS: There were 604 CVD and 1868 all-cause deaths, respectively. Compared with the metabolically healthy nonobese participants, their obese counterparts were not at elevated risk of CVD [hazard ratio (HR) 1.26, 95% confidence interval (CI) 0.74–2.13], although both nonobese (HR 1.59, 95% CI 1.30–1.94) and obese (HR 1.64, 95% CI 1.17–2.30) participants with two or more metabolic abnormalities were at elevated risk. Metabolically unhealthy obese participants were at elevated risk of all-cause mortality compared with their metabolically healthy obese counterparts (HR 1.72, 95% CI 1.23–2.41). CONCLUSION: Metabolically healthy obese participants were not at increased risk of CVD and all-cause mortality over 7 yr.